How Can Law and Policy Advance Quality in Genomic Analysis and Interpretation for Clinical Care?. Issue 1 (March 2020) - Evans, Barbara J.; Javitt, Gail; Hall, Ralph; Robertson, Megan; Ossorio, Pilar; Wolf, Susan M.; Morgan, Thomas; Clayton, Ellen Wright; ,
Delivering high quality genomics-informed care to patients requires accurate test results whose clinical implications are understood. While other actors, including state agencies, professional organizations, and clinicians, are involved, this article focuses on the extent to which the federal agencies that play the most prominent roles — the Centers for Medicare and Medicaid Services enforcing CLIA and the FDA — effectively ensure that these elements are met and concludes by suggesting possible ways to improve their oversight of genomic testing.